2020
DOI: 10.1016/j.jcmg.2019.02.028
|View full text |Cite
|
Sign up to set email alerts
|

5-Year Prognostic Value of Quantitative Versus Visual MPI in Subtle Perfusion Defects

Abstract: OBJECTIVES-We aimed to study the ability of automated myocardial perfusion imaging analysis in comparison to visual analysis in major adverse cardiac events (MACE) prediction. BACKGROUND-Quantitative analysis has not been compared to clinical visual analysis in prognostic studies. METHODS-From the multi-center REgistry of Fast Myocardial Perfusion Imaging with NExt generation SPECT (REFINE SPECT), 19,495 patients (64±12 years, 56% male) undergoing stress Tc-99m SPECT-MPI were followed for 4.5±1.7 years for MAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 30 publications
1
47
0
Order By: Relevance
“…Notably, patients with more than 0 but less than 1% TPD had a 40% higher risk of events than patients with a TPD of 0, demonstrating the importance of even small deficits, which may be missed without the higher spatial resolution of new solid-state SPECT cameras (Fig. 7) (67). The registry has also allowed researchers to perform various collaborative projects, including the development of novel machine learning methods tailored for the analysis of solid-state SPECT MPI and subsequent integration of quantitative image data variables with prescan clinical information.…”
Section: Large-scale Clinical Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, patients with more than 0 but less than 1% TPD had a 40% higher risk of events than patients with a TPD of 0, demonstrating the importance of even small deficits, which may be missed without the higher spatial resolution of new solid-state SPECT cameras (Fig. 7) (67). The registry has also allowed researchers to perform various collaborative projects, including the development of novel machine learning methods tailored for the analysis of solid-state SPECT MPI and subsequent integration of quantitative image data variables with prescan clinical information.…”
Section: Large-scale Clinical Validationmentioning
confidence: 99%
“…The increasing clinical use of solid-state SPECT camera systems has led to a large body of evidence validating their prognostic and (67). Notably, patients with more than 0 but less than 1% TPD had a 40% higher risk of events than patients with a TPD of 0, demonstrating the importance of even small deficits, which may be missed without the higher spatial resolution of new solid-state SPECT cameras (Fig.…”
Section: Large-scale Clinical Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing evidence, including large multicenter studies, that these solid-state SPECT systems demonstrate excellent diagnostic and prognostic utility in cardiac imaging. [6][7][8] In the last few years, the equipment companies have also introduced general-purpose CZT-based SPECT systems to enable applications other than cardiac imaging. These cameras benefit from improved energy and image resolution due to the CZT detectors and have demonstrated improved image quality in early clinical implementation as compared to general-purpose Angerbased systems.…”
mentioning
confidence: 99%
“…[29][30][31] In a large multicenter study, we showed that TPD allows more precise risk gradation for MACE, even in categories traditionally considered normal. 32 However, most MPI risk-stratification studies used perfusion defect size alone, without considering other imaging (PET flow, CAC), stress test, or clinical variables-or considered only subset of these variables. While physicians mentally attempt to combine all stress test and clinical variables when interpreting MPI, such integration is subjective and affected by individual bias and expertise.…”
mentioning
confidence: 99%